1997
DOI: 10.1152/jn.1997.77.3.1614
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Spine Density and LTP Induction in Cultured Hippocampal Slices

Abstract: Transverse hippocampal slices were cut from 8- to 9-day-old rats and maintained in an interface chamber for periods of 1-4 wk, in tissue culture conditions. Neurons in the slice preserved their spatial organization and connectivity. Dendritic spine density in CA1 neurons was very low at 1 wk in culture, and long, filopodia-like structures were abundant. Spine density increased in these neurons nearly threefold during the course of 3 wk in vitro, to approach values of those of the normal, in vivo hippocampus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 33 publications
8
69
1
Order By: Relevance
“…Ref. 63) we found that spine density was lower in our organotypic hippocampal slice cultures after 5-6 DIV as compared with perfused mouse brain at 2, 4, and 8 weeks of age by a factor of 4 -5. This low spine density is likely at least in part due to differences in the actual developmental stages of organotypic slice cultures versus in vivo as it increases strongly after 3-4 weeks in culture (63).…”
Section: Ratio Of Ampar-epsc To Nmdar-epsc Is Increased In Young D36supporting
confidence: 51%
See 1 more Smart Citation
“…Ref. 63) we found that spine density was lower in our organotypic hippocampal slice cultures after 5-6 DIV as compared with perfused mouse brain at 2, 4, and 8 weeks of age by a factor of 4 -5. This low spine density is likely at least in part due to differences in the actual developmental stages of organotypic slice cultures versus in vivo as it increases strongly after 3-4 weeks in culture (63).…”
Section: Ratio Of Ampar-epsc To Nmdar-epsc Is Increased In Young D36supporting
confidence: 51%
“…63) we found that spine density was lower in our organotypic hippocampal slice cultures after 5-6 DIV as compared with perfused mouse brain at 2, 4, and 8 weeks of age by a factor of 4 -5. This low spine density is likely at least in part due to differences in the actual developmental stages of organotypic slice cultures versus in vivo as it increases strongly after 3-4 weeks in culture (63). This observation also illustrates the importance of the analysis of spine density in perfused brain, which reflects the actual in vivo situation, and of the analysis of synaptic transmission in acute hippocampal slices, as described above.…”
Section: Ratio Of Ampar-epsc To Nmdar-epsc Is Increased In Young D36mentioning
confidence: 49%
“…Semi‐automatic analysis performed with the Filament tracer software revealed that spine density on apical dendrites represented on average 3.21 spines/10 μm (Figure 5b). These values were lower than in another study carried out on 8 to 9‐day‐old rats showing that after 2 and 3 weeks in culture average spine density was 7 and 11 spines/10 μm respectively (Collin, Miyaguchi, & Segal, 1997). This difference may occurs a result of age of the sacrificed neonate rats, which were older in this work, and also to the analysis method used.…”
Section: Discussioncontrasting
confidence: 63%
“…Cdk5 activity is known to regulate the morphogenesis of dendritic spines, the major sites of excitatory synaptic transmission in the CNS, thus influencing the function of neuronal circuits (6,47,48). Under pathological conditions, dendritic spine loss, representing synaptic damage, is known to correlate with the degree of cognitive decline in AD (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%